Records of the Society for the Propagation of the Gospel In Foreign Parts - Society for the Propagation of the Gospel in Foreign Parts (Great Britain)
Correspondence relating to the work of the society and to prayer-books and Bibles printed in Cambridge, England. Correspondents include Robert Carter Nicholas and John Waring.
Photocopies.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Nicholas, Robert Carter, -- 1728-1780 -- Correspondence; Waring, John -- Correspondence; Bible -- Publication and distribution -- England -- Cambridge; Bible -- Publication and distribution -- Societies, etc; Prayer books